Inequality in China: Development, transition, and policy - Shi Li; Terry Sicular; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this paper we describe the major trends in China's income inequality over the past 40 years and explain them as the outcome of four interleaved stories. The first story is a standard development story characterized by structural change, market development, labour absorption, and the Kuznets inverted-U path of inequality. The second is the economic transition story, in which changes in income distribution result from the shift from plan to market. Third is incomplete transition, with opportunities for rent-seeking, corruption, and hidden income. Fourth is the story of government efforts to moderate inequality through social and welfare policies.
Keywords: D31; O15; O53; P20; 330; China; inequality; development; transition; welfare policy